Promoting pedestrianization in the central business districts of Davao City through park-and-ride facilities - Obeña, Jed Clinton D.; Villaseca, Maria Rallah E. (2014)
One of the most essential parts of the city is its Central Business Office (CBO) which ironically, carries a myriad of issues to resolve. It is best to resolve the issues before it takes its toll on the city and result to more serious problems. For this reason, the proponent of this study is looking at increasing the level of Pedestrianization in the CBD of Davao City with a desire to protect the city from urban decline. Through the implementation of a Park and Ride (P&R) facility, on-street parking will be minimized giving pedestrians more space to move around the CBD hence, the CBD becomes pedestrianized. Moreover, the implementation of P&R facility will also alleviate traffic congestion. In this thesis, the proponent will identify the major CBD in Davao using the Overlay Analysis Method (OAM) with the following qualifiers: zonal value, infrastructure density, commerce activity, traffic congestion, user?s perception and street layout. Upon identifying the major CBD, the best locations for the Park & Ride Facility will be identified also by using OAM with the following criteria: lack of parking facility, away from nodes, nearness to landmarks and walking distances from nodes and proximity to the routes of public transportation or the application of Place Legibility by Kevin Lynch. The locations will be assessed and evaluated for the reconstruction of a P & R facility. Along with the construction of P&R facility, the streets of the CBD will be improved by incorporating sustainable Green Urban Design Principles to make the streets more conducive for walking, especially the common paths that are regularly traversed by pedestrians. Once all these things are in place., the mobility in the CBD will improve and pedestrians will be encouraged to walk along the streets of the CBD altogether contributing to the preservation of Davao?s image, ?Life is here?.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2014